2022
DOI: 10.18502/kss.v7i10.11367
|View full text |Cite
|
Sign up to set email alerts
|

Click CWLS as a Solution to Improve Community's Understanding of Sukuk Linked Sukuk Cash Products

Abstract: The Indonesian government has issued an innovative Islamic philanthropy-based sharia investment product in the form of Cash Waqf Linked Sukuk (CWLS). This study aims to: (1) Analyze the level of public understanding of CWLS. (2) Provide solutions to improve community literacy related to CWLS. (3) Provide a digital platform design that makes it easier for the public to access information and to buy CWLS products. The research method used is descriptive qualitative. Sources of data are primary data obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…Through this research, it is revealed that CWLS has the potential to encourage society to achieve more sustainable and equitable economic growth. Mukti et al (2022) analyzed the level of public understanding of CWLS, provided solutions to improve public literacy related to CWLS, and provided a digital platform design that makes it easier for people to access information and buy CWLS products. The results found that the understanding of the Muslim community in Yogyakarta about CWLS is still very low at 17.8%.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The potential of existing crowdfunding platforms with the number of worldwide crowdfunding platforms reached around 1,250 units, raising funds amounting to USD 34.4 billion in 2015 and USD 16.2 billion in 2014 (Akbar 2014). As research conducted by Mukti et al (2022) and (Berakon, Aji, and Hafizi 2021) states that with a digital platform that is integrated with mobile banking, Islamic banking is expected to be able to provide complete information about CWLS while increasing waqf literacy to the public so that this can make it easier for people who want to make waqf through CWLS.…”
Section: Fourth Priority: Creating a Crowdfunding Platform For Cwls I...mentioning
confidence: 99%